A Case of Severe Early Childhood Caries Occurring in a Childhood Cancer Patient - Tatsuya Akitomo; Noriko Niizato; Shunya Ikeda; Yuya Ito; Eimi Tabata; Chieko Mitsuhata; Ryota Nomura (Children)
Background/Objectives: Childhood cancer is the leading cause of death among children, although medical advances are improving the prognosis. During cancer treatment, nausea or vomiting may occur and eating habits may become irregular; therefore, it is important to prevent the development of oral diseases. We encountered a childhood cancer patient with rapidly progressive multiple dental caries, and this report describes the progress. Methods: A boy aged 2 years 9 months was referred for perioperative oral management. No caries were detected in the oral cavity at the initial visit. Results: As the patient had difficulty eating because of nausea and vomiting during cancer treatment, he began to consume probiotic drinks frequently. At 8-month follow-up, dental caries localized to the primary molars was detected. However, caries had occurred in all erupted teeth by 9 months later, confirming the diagnosis of severe early childhood caries. Dental treatment and long-term oral management contributed to good oral health except for dental abnormalities caused by chemotherapy. Conclusions: Childhood cancer patients, particularly at an early age, are at risk of rapid deterioration of oral disease even over a short time period. It is important to cooperate with medical or dental professionals from other hospitals to provide dietary and oral health instruction and continue long-term oral management to improve patients’ quality of life.